2015
DOI: 10.1080/10584609.2014.969463
|View full text |Cite
|
Sign up to set email alerts
|

Countering Implicit Appeals: Which Strategies Work?

Abstract: Some contemporary politicians try to mobilize racial attitudes by conveying implicit racial messages against their opponents-messages in which the racial reference is subtle but recognizable and which attack the opponent for alleged misdeeds. Although targeted politicians have tried a number of different strategies to respond to implicit racial appeals, little is known about the effectiveness of these strategies. Using two survey experiments, we answer the following question: Does calling the appeal "racial" w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In sum, there remains substantial disagreement about whether and why the IE model holds for contemporary anti‐black racial appeals. While some studies have found that it does (Nteta et al, ; Tokeshi & Mendelberg, ), others have found evidence that it does not (Huber & Lapinski, ; Hutchings et al, ; Valentino, Neuner, et al, ). Expanding on this existing work, we posit several factors that could be leading to the null results that we and other scholars have found.…”
Section: The Ie Model and Anti‐black Appealsmentioning
confidence: 99%
See 4 more Smart Citations
“…In sum, there remains substantial disagreement about whether and why the IE model holds for contemporary anti‐black racial appeals. While some studies have found that it does (Nteta et al, ; Tokeshi & Mendelberg, ), others have found evidence that it does not (Huber & Lapinski, ; Hutchings et al, ; Valentino, Neuner, et al, ). Expanding on this existing work, we posit several factors that could be leading to the null results that we and other scholars have found.…”
Section: The Ie Model and Anti‐black Appealsmentioning
confidence: 99%
“…When explicitly recognized as racial, however, such appeals activate the public's adherence to egalitarian norms, which attenuate the influence of racial predispositions on subsequent evaluations. The IE model has held up to numerous empirical tests from the late 1990s to the very recent past (Mendelberg, 1997(Mendelberg, , 2001Nteta et al, 2015;Tokeshi & Mendelberg, 2015;Valentino et al, 2002).…”
Section: The Ie Model and Anti-black Appealsmentioning
confidence: 99%
See 3 more Smart Citations